1997
DOI: 10.1046/j.1469-8137.1997.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of copper on iron acquisition processes in Plantago

Abstract: (This paper is dedicated to the memory of Professor Horst Marschner) SUMMARY In Plantago lanceolata L. the effect of Cu(II) additions to the nutrient solution on root-associated Fe(III) reductase was studied in a factorial design with different Cu(II) and Fe(III) concentrations. Iron starvation resulted in approx. an eightfold increase in root Fe reduction at the level of intact plants and twofold enhancement in the specific activity of both NADH-linked FeEDTA reductase and H^-ATPase in isolated root plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 30 publications
(12 reference statements)
1
18
0
2
Order By: Relevance
“…The third phase of the curve indicates Cu toxicity, which abolished ferricchelate reductase activity. Similar inhibition of ferric-chelate reductase activity by high Cu has been observed in cucumber 34 and Plantago lanceolata, 30 but high Cu did not inhibit ferric-chelate reductase protein activity in Plantago membrane isolates, which suggested that Cu blocked expression rather than function of the ferric reductase.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…The third phase of the curve indicates Cu toxicity, which abolished ferricchelate reductase activity. Similar inhibition of ferric-chelate reductase activity by high Cu has been observed in cucumber 34 and Plantago lanceolata, 30 but high Cu did not inhibit ferric-chelate reductase protein activity in Plantago membrane isolates, which suggested that Cu blocked expression rather than function of the ferric reductase.…”
mentioning
confidence: 52%
“…A similar inhibition for whole root ferric-chelate reductase activity by low Cu was observed for Plantago lanceolata. 30 In pumpkin, and in cucumber supplied with 0.5 µM Fe, 0 Cu was optimal. As Cu was increased above optimal concentrations, lower ferric-chelate reductase activity occurred.…”
mentioning
confidence: 99%
“…Portanto, apesar de os teores de Fe nas raízes e na parte aérea terem sido elevados pelo excesso de Cu em solução, esse exerceu alta interferência na translocação do Fe, podendo ser uma das possíveis causas da toxidez do Cu para o eucalipto. O efeito fitotóxico do Cu sobre a translocação de Fe também foi observado em espécies de Plantago em estudo realizado por Schmidt et al (1997).…”
Section: Parte Aérea Raizunclassified
“…Seedlings were grown hydroponically in a climatecontrolled glasshouse as described in Schmidt et al (1997). Seeds were germinated in quartz sand moistened with tap water.…”
Section: Growth Conditionsmentioning
confidence: 99%